The Effects of Heating Temperatures on Passion Fruit Juice's Ascorbic Acid and Total Phenol Levels - Siswandi, Alodia Jeconiah; Prismawan, Deka; Kambira, Pretty Falena Atmanda (Universitas Muhammadiyah Yogyakarta, 2023)
The Passiflora edulis f. flavicarpa, a yellow passion fruit, is known for its distinctive aroma and tart flavor. The pulp of the yellow passion fruit can be used to make tea, jam, and syrup commercially. Commercial items are processed using oven heating, which involves prolonged exposure to high temperatures. As a result, fruit content, particularly water content, may alter. The benefit of reducing the water content is that less microbial growth medium means the product has a longer shelf life. However, fruit flesh’s nutritional composition will also change due to the ascorbic acid and phenolic compounds' thermolability and other factors. In this study, the yellow passion fruit pulp juice is heated in a controlled manner at 60°C, 70°C, and 80°C for 7 hours using an oven. The purpose is to assess changes in the amounts of ascorbic acid and total phenol that occurred. A paired T-test was used to assess the association between weight loss, ascorbic acid levels, and phenolic levels in the control and treatment groups. The amount of ascorbic acid was determined using the 2.6 dichloroindophenol titrimetry method, and the amount of phenol was determined using the Folin-Cioceltau method and UV-Vis spectrophotometry. According to this study, increasing the temperature to 60 °C or 80 °C significantly reduces weight and ascorbic acid levels. Also, the heating temperature unaffected the amount of phenol in each group.